The Influence of Organizational Commitment and Work Environment on Employee Performance Mediated By Job Satisfaction (Empirical Study: Employees at PT. Global Loyalty Indonesia) - Arisandi, Bagus; Heryjanto, Andreas (Green Publisher Indonesia, 2024)
Employee performance is an important factor for companies in achieving their goals. Several factors influence employee performance, including organizational commitment, work environment, and job satisfaction. This study aims to determine the effect of organizational commitment and work environment on employee performance mediated by job satisfaction at PT Global Loyalty Indonesia. The research method used is a quantitative method. This study employs Structural Equation Modeling (SEM) data analysis techniques with the Smart-PLS application. The population size is 241 employees, and the sample size to be taken is 112 respondents. The data collection technique used in this study is a questionnaire. The results of the study indicate that the variables of organizational commitment, work environment, and job satisfaction have a positive and significant effect on employee performance. In addition, organizational commitment and work environment also have a positive and significant effect on job satisfaction. The results of the indirect effect test indicate that the job satisfaction variable mediates the relationship between organizational commitment and employee performance and also mediates the relationship between the work environment and employee performance. This study provides practical implications for companies to always pay attention to the work environment so that employees can work safely and comfortably so that job satisfaction can increase which ultimately affects their performance.